Knowledge and attitude towards Mpox among healthcare workers: an intervention study - Sally Khattab; Nader Nemr; Rania Kishk; Hebatalla Aly; Nada Nemr; Amira El-Ghazaly; Mohamed Abdalla; Noha Elsaid (Microbes and Infectious Diseases)
Background: Health care workers lack knowledge about human Mpox, and most are not confident in their abilities to identify and manage cases. The study's objectives are to improve healthcare workers ' knowledge and attitudes regarding Mpox infections and to help them become confident in diagnosis and management. Methods: This study was carried out in two stages. The first phase involved a cross-sectional survey of 206 healthcare workers, utilizing the snowball sampling approach, to evaluate their knowledge and attitudes regarding Mpox using a self-administered questionnaire. The second phase was a pre-posttest study with stratified random sampling method to improve the participants’ knowledge and attitude towards Mpox among health care workers. Results: In phase one, 7.3% of the 206 participants had good knowledge with a mean knowledge score of 6.2 ± 8.3., and 89.3% had a positive attitude. In phase two, there was significant improvement in the score of knowledge post intervention immediately [28.6 ± 1.7] and after one month [28.5 ± 1.4] compared with before. The improvement in knowledge level was from 5.7% before to 100% after the intervention. The positive attitude frequency also increased from 42.9% to 100% [p < 0.001]. Conclusion: In conclusion the knowledge and attitude level towards human Mpox infection in our study were considered low. After giving the educational training program, the participants’ knowledge and attitude towards Mpox among health care workers was improved.